Cytochrome P450‐encoding genes from the Heliconius genome as candidates for cyanogenesis. Issue 5 (3rd July 2013) - Chauhan, R.; Jones, R.; Wilkinson, P.; Pauchet, Y.; ffrench‐Constant, R. H.
Abstract: Cytochrome P450s are important both in the metabolism of xenobiotics and the production of compounds such as cyanogenic glucosides, which insects use in their defence. In the present study, we use transcriptomic and genomic information to isolate and name P450‐encoding genes from the butterfly Heliconius melpomene . We classify each of the putative genes into its appropriate superfamily and compare the distribution of P450s across sequenced insects. We also identify homologues of two P450s known to be involved in cyanogenesis in the six‐spot Burnet moth, Zygaena filipendulae . Classification of Heliconius  P450s should be an important step in the dissection of their role in the exploitation of their host plant, the passion vine Passiflora .